Tricuspid regurgitation: long-term management, morbidity and mortality. (25th November 2020) - Marquez Camas, P; Rodriguez Capitan, J; Chaparro Munoz, M; Lopez Haldon, J; Manovel Sanchez, A; Becerra Munoz, V.M; Doncel Abad, V; Melgar Melgar, A; Robles Mezcua, A; Jimenez Navarro, M
Abstract: Introduction: The natural history of tricuspid regurgitation (TR) is poorly known and its morbi-mortality has been rarely described. Objectives: Several causes lead to the appearance of TR. The aim of our study was to assess the prognosis of our patients taking into account the etiology and severity of their valvulopathy. We also wanted to evaluate the income-free survival. Methods: We designed a bi-centre (including a tertiary-level hospital and a secondary hospital), descriptive and retrospective study that included 745 patients with at least moderate-to-severe TR who had not had any previous cardiac surgery for this pathology. Once patients were selected, clinical characteristics (age, sex, cardiovascular risk factors) as well as associated pathology, readmissions because of heart failure and mortality were evaluated. Results: 745 patiens were included in the study (70.7% women) from the year 2002 to the 2017. The age average was 72.28 years old (in a range of 16–97). The obtained frequency of primary TR (caused by an abnormality of any of the components of the TV apparatus) was 6.4%, secondary TR (due left-sided valvular and myocardial diseas, Pulmonary hypertension or increased RV afterload) was 67.6%, related to AF 19% and isolated TR 7%. After a long follow-up (global median survival 51.51 months) only 62 patients received surgical treatment. Figures 1–4 show survival curves depending on etiology. Figure 5 compares survival curves depending on sex characteristics. Conclusions: TR (moderate-to-severe or more) was associated with poor outcomes from the beginning of the follow-up. This poor clinical prognosis was observed in all ethiological groups analyzed and in both genders. Funding Acknowledgement: Type of funding source: Foundation. Main funding source(s): Sociedad Andaluza de Cardiología